Endosulfan Induced Changes in the Liver and Ovary of the Freshwater Fish, Oreochromis mossambicus (Trewaves) - T.S, Saravanan; R, Chandrasekar; M. Aneez, Mohamed (Malaysian Journal of Science, 2003)
The freshwater fish, $Oreochromis$ $mossambicus$ on exposure to sublethal concentration (0.001ppm) of the insecticide endosulfan (Technical Grade 99% pure) for two periods of 30 and 60 days each, showed significant alterations in the organic constituents of blood, liver and ovary, and histopathological changes in the liver and ovary. Results revealed hyperglycemic condition in the fish after 30 days of exposure and hypoglycemic condition after 60 days of exposure. The sugar level in the liver and ovary decreased after 30 and 60 days of exposure respectively. The free amino acid level in blood and liver increased after 30 days of exposure. Whereas after 60 days of exposure, the level declined in both tissues. Free amino acid level of ovary decreased significantly in both the periods of exposure. The protein content of liver and ovary decreased after 30 days of exposure, but in the ovary it increased after 60 days of exposure. In all the tissues, the cholesterol level increased significantly after both periods of exposure. The reasons for significant alterations in the organic constituents of tissues are discussed. Histological studies reveal that the liver and ovary of control fish were normal. The fish on exposure to endosulfan for 30 days exhibited changes like cell vacuolation, histolysis and necrosis. The changes became more prominent after 60 days of exposure. The exposure to endosulfan for 30 days resulted in the degeneration of the immature oocytes and rupture of follicular epithelium. These changes became intense and the oocytes ruptured after 60 days of exposure. Thus the fish on exposure to endosulfan showed both nutritive and reproductive losses.